The Effects of Organizational Resilience, Employee Well-Being, and Leadership Style on Employee Performance at CV. SM Putra Kediri - Vivin Ulfadlotul Mufarida; Mahyudi, Beny (Universitas Muhammadiyah Pontianak, 2026)
This study analyzes the influence of organizational resilience, employee well-being, and leadership style on employee performance. The objective is to evaluate the relationship between these three variables, both partially and simultaneously. The methodology employed is a quantitative approach that combines descriptive and thematic analysis. The findings indicate that organizational resilience, employee well-being, and leadership style have a statistically significant effect on employee performance, with a significance level of 0.002 (<0.05) and a calculated F-value of 7.597 exceeding the critical F-value of 2.48. Implicitly, a holistic improvement in these three factors is crucial for optimizing employee productivity and performance. Keywords: Organizational Resilience; Employee Well-Being; Leadership Style; Employee Performance